Numerical Effectiveness of Models and Methods of Integration of the Equations of Motion of a Car - Marek Szczotka; Szymon Tengler; Stanislaw Wojciech (Differential Equations and Nonlinear Mechanics)
The paper presents models of car dynamics with varying complexity. Joint coordinates and homogenous transformations are used to model the motion of a car. Having formulated the models of the car, we discuss the influence of the complexity of the model on numerical efficiency of integrating the equations describing car dynamics. Methods with both constant and adaptive step size have been applied. The results of numerical calculations are presented and conclusions are formulated.